Praktik akuntansi lingkungan dan biaya modal pada perusahaan di Indonesia - Sari, Sari Dewi; Aling, Aling (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Observe the development of social responsibility, especially in the field of environment, and the performance of corporate governance in Indonesia are important factors in the company's operations. A number of companies do not participate in this disclosure activity, which will result in new costs that will be borne by the company. The high and low cost of capital owned by a company will show how much risk the company will accept in order to obtain funding for the company's sustainability. This research was conducted to produce an analysis of the effect of the level of environmental accounting practices on the cost of equity capital or the cost of debt capital and the effect of corporate governance performance on the cost of equity capital or the cost of debt capital. This study uses data on financial statements and sustainability reports of companies listed on the Indonesia Stock Exchange from 2016 to 2020. The test results show that financial environmental accounting practices and corporate governance performance consist of block ownership, board size, gender diversity, and board tenure. has a significant effect on the cost of equity capital. on the cost of debt capital, only the board size variable has a significant effect. This research encourages companies to be able to participate in the disclosure of environmental performance and corporate governance.